2014
DOI: 10.1097/wnf.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine Augmentation Therapy for Obsessive Compulsive Patients Resistant to SSRIs—An Open-Label Study

Abstract: AMN adjunction to SSRI treatment may lead to a significant reduction in OC symptoms, supporting the hypothesis that transduction of the glutamate signal via NMDA receptor may play a role in OCD. A large scale, double-blind, placebo-controlled study is warranted to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The Y-BOCS is rated by clinicians and has proven validity and reliability for measuring OCD symptoms [32,33]. OCD severity is defined using Y-BOCS total score as extreme (score 32-40), severe (score 24-31), moderate (16)(17)(18)(19)(20)(21)(22)(23), and mild (8)(9)(10)(11)(12)(13)(14)(15) [33]. In the present study, the Y-BOCS was used to quantify the severity of OCD and evaluate treatment response, defined as ≥ 35 % reduction in Y-BOCS total score [34].…”
Section: Yale-brown Obsessive Compulsive Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The Y-BOCS is rated by clinicians and has proven validity and reliability for measuring OCD symptoms [32,33]. OCD severity is defined using Y-BOCS total score as extreme (score 32-40), severe (score 24-31), moderate (16)(17)(18)(19)(20)(21)(22)(23), and mild (8)(9)(10)(11)(12)(13)(14)(15) [33]. In the present study, the Y-BOCS was used to quantify the severity of OCD and evaluate treatment response, defined as ≥ 35 % reduction in Y-BOCS total score [34].…”
Section: Yale-brown Obsessive Compulsive Scalementioning
confidence: 99%
“…glutamate levels in cerebrospinal fluid, glutamatergic over-activity, and polymorphism of gene coding N-methyl-D-aspartate (NMDA) receptor are shown to contribute to OCD occurrence [11][12][13][14]. In addition, there is a large body of evidence on the clinical benefits of augmentation therapy with glutamate-modulating agents such as riluzole, N-acetylcysteine, ketamine, and amantadine in reducing symptoms in SRI-refractory OCD [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…reported that a treatment‐resistant patient with OCD responded to amantadine (200 mg/day) added to clomipramine (225 mg/day) . In an open‐label study of amantadine in eight OCD patients who had failed one SSRI trial, significant reductions in total Y‐BOCS (28 ± 4.5 vs 18.8 ± 8.8; P < 0.01; d.f. = 7; t = 2.36), Y‐BOCS Compulsion subscale (15.3 ± 3.2 vs 10.6 ± 4.7; P < 0.02; d.f.…”
Section: Discussionmentioning
confidence: 99%
“…58 Pasquini et al reported that a treatment-resistant patient with OCD responded to amantadine (200 mg/day) added to clomipramine (225 mg/day). 59 In an open-label study of amantadine in eight OCD patients who had failed one SSRI trial, 28 This study has some limitations that need to be addressed as they may impair interpretation of the findings. First, due to ethical considerations, there was no placebo-only group in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation